1984
DOI: 10.1901/jaba.1984.17-229
|View full text |Cite
|
Sign up to set email alerts
|

The Training and Generalization of Social Interaction Skills With Autistic Youth

Abstract: Two experiments were conducted to increase the initiations and duration of social interactions between autistic and nonhandicapped youths. Experiment 1 taught two autistic youths to initiate and elaborate social interactions with three age-appropriate and commonly used leisure objects; a radio, a video game, and gum. The students were first taught to use the objects and subsequently instructed in the related social skills. The youths generalized these social responses to other nonhandicapped peers in the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
93
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(96 citation statements)
references
References 13 publications
(21 reference statements)
2
93
0
1
Order By: Relevance
“…Because children with autism have difficulties with generalizing behaviour and skills between settings [26], we wanted to design the autistic children's interactions with both the robot and the human adult to be as similar as possible in order to ensure the highest likelihood of skill transference between the two settings. To this end, we used a humanoid robot known as KASPAR [14] (see Fig.…”
Section: Novel Pilot Studymentioning
confidence: 99%
“…Because children with autism have difficulties with generalizing behaviour and skills between settings [26], we wanted to design the autistic children's interactions with both the robot and the human adult to be as similar as possible in order to ensure the highest likelihood of skill transference between the two settings. To this end, we used a humanoid robot known as KASPAR [14] (see Fig.…”
Section: Novel Pilot Studymentioning
confidence: 99%
“…In addition, teachers may arrange their classrooms in ways that make social activities motivating, which encourages children to initiate social behaviors (McGee, Morrier, & Daly, 1999). Studies have indicated that using teacher-mediated or one-to-one teaching techniques to initiate social interactions prior to practicing them with peers increases the frequency and duration of interactions (GaylordRoss & Haring, 1987;Gaylord-Ross, Haring, Breen, & Pitts-Conway, 1984). reviewed several behavioral strategies used with individual children to increase their social interactive skills.…”
Section: Individual Instructionmentioning
confidence: 99%
“…Unfortunately, although the training of syntactically correct initiations has been demonstrated, there are few examples of studies showing turn-taking or communicative exchanges beyond one or two utterances (Gaylord-Ross, Haring, Breen, & PittsConway, 1984). In our research, we taught such skills to students who had difficulty in initiating and maintaining conversational exchanges.…”
mentioning
confidence: 97%